Estetika Pada Interior Restoran Ramen Nozomi dan Tomoto di Surabaya - Stephanie Stephanie; laksmi kusuma wardani (Intra, 2014)
Nowadays, as societies are swarmed by modernism; restaurants become a lifestyle and common habit in daily life. Japanese restaurants are chosen to be the samples of this research as Japan stands in its traditional cultures. In this research, some requirements are set-up to choose the samples used, those are: restaurants must be independent and aren’t franchised, have good reputations, have their own systems, and writer’s personal interests over the objects. Ramen Nozomi and Tomoto are chosen as research samples, as those restaurants matched-up the requirements stated above. Research is done to understand how aesthetic values and the effects toward the interior ambience of each objects. E.B.Feldman’s aesthetic theories are used as the main approach of this research, that both visual form and aesthetic structure are associated with aesthetic. Qualitative descriptive research method is used to decipher the datas collected in details; in which the datas come from documentation, location observations, and interviews. The result showed the practice of aesthetic values; in which matched-up with E.B.Feldman’s theories on the varieties of elements and principals of design. Thus, different ambiences are formed over each areas; which affects users’ aesthetic experiences.